THE ROLE OF TECHNOLOGY IN TEACHERS' CREATIVITY DEVELOPMENT IN ENGLISH TEACHING PRACTICES - Fitriah, Fitriah (TEFLIN Journal, 2018)
This study investigates teachers' views on the role of technology in building their creativity during teaching practices within the context of Indonesian higher education. An exploratory mixed methods design was employed by interviewing 20 EFL teachers about the role of technology in teachers' creativity and administering a creativity questionnaire to 175 teachers. The findings revealed that teachers are aware of the importance of technology in creativity. Technology appears to help them explore their creativity and encourages learners' creativity in a way that it helps transfer their creativity into reality, makes the activities more authentic, and provides teaching materials on various topics. However, there is no clear evidence about how these teachers use technology in their actual classrooms. In general, the way in which technology was utilized in teaching was limited and largely influenced by other factors, such as teachers' willingness to learn, students' participation, frequent interaction, and cooperation. This implies the need for future research to investigate the creative pedagogy of technology use in the classroom to contribute to improving classroom practices with regard to creativity and technology use.